Scope of Quantitative Research under Faculty of Education - KC, Agni (BMC Research Journal, 2025)
Present research work deals with the details of quantitative research. It shows a deep and detail explanation and inclusion of scholarly definitions and concluding ideas in the introduction section. Moreover, the next part deals with its characteristics, objectives of the methodology. The study further reveals quantitative methods can be categorized into survey research, co relational research, experimental research and causal-comparative research. It involves the utilization and analysis of numerical data using specific statistical techniques to answer questions like whom, how much, what, where, when, and how. It also describes the methods of explaining an issue or phenomenon through gathering data in numerical form. This research work concludes that quantitative research has got high validity and its scope is increasing at present.